Practical fermentation technology. - McNeil, Brian, ....-; Harvey, Linda M., ....- (Chichester : Wiley, 2008)
1 Fermentation: An Art from the Past, a Skill for the Future. 2 Fermentation Equipment Selection: Laboratory Scale Bioreactor Design Considerations. 3 Equipping a Research Scale Fermentation Laboratory for Production of Membrane Proteins. 4 Modes of Fermenter Operation. 5 The Design and Preparation of Media for Bioprocesses. 6 Preservation of Cultures for Fermentation Processes. 7 Modelling the Kinetics of Biological Activity in Fermentation Systems. 8 Scale Up and Scale Down of Fermentation Processes. 9 On-line, In-situ, Measurements within Fermenters.
Keywords: Technische microbiologie